ANALISIS HUBUNGAN DAN PENGARUH DAN PENGARUH LINGKUNGA KERJA DAN DISIPLIN KERJA TERHADAP KINER-JA KARYAWAN PADA PT. JAYA BERSAMA SAPUTRA PERKASA ATAU FORTRESS - Yortan Kusa; Anthon P.W. Nomleni (Universitas Dian Nuswantoro, 2022)
This study aims to determine the relationship and influence of the work environment and work discipline on the performance of employees of PT. Jaya with Saputra Mighty. This study used a quantitative descriptive method with a sample of 113 people who were all employees of PT. Jaya with the mighty Saputra. Data col-lection uses a questionnaire that has been tested for validity and reliability. Data analysis techniques were performed using non-parametric statistics, data processing using SPSS (statistical product and service solu-tion) IMB version 26. The results of the research based on the t test on the work environment and work disci-pline show that: 1) the work environment relationship has a positive and significant effect on employee per-formance at PT. Jaya Bersama Saputra Perkasa. 2) the relationship of work discipline has a positive and significant effect on employee performance at PT. Jaya Bersama Saputra Perkasa. 3) the relationship be-tween work environment and work discipline has a positive and significant influence simultaneously on the performance of employees at PT. Jaya Bersama Saputra Perkasa.